(untitled) (American Journal of Pedagogical and Educational Research, 2025)
Organizations exist to actualize the purpose for which it was formed. The goals are achieved when people work as either formal or informal group or organization. Employees like to interact with their co-workers to ensure that job related problems are solved with collective ideas to enhance job performance. Organization is goal-directed, boundary-maintaining, and a system of consciously coordinated activities that involves formal structures, planning, division of labour, and leadership to achieve specific goals. Formal and informal organizations function in the same environment, the informal organization is created within the formal organization to protect the interest of members. The formal organization is consciously and carefully planned with the coordination of activities to ensure effectiveness and efficiency. This paper tends to clarify the differences between formal and informal organizations. When organization manages the informal group, there is the tendency of reducing conflict among the workforce, the cooperation may enhance teamwork and organizational performance. Managers and leaders should recognize the existence of informal group or organization by having periodic conversations with them so as to gather authentic information about the performance of the organization.